Landscape ecological risk assessment and transformation processes in the Guinean-Congolese climate zone in Benin Republic (2023)
The landscape of Ramsar site 1018 in Benin Republic is increasingly modified by different types of land use. Understanding these changes dynamics is essential for efficient resource management. The aim of the research is to identify the spatial configuration of landscapes using landscape indices, which are the indicators and guide for agricultural policy. Fragstats 4 software helped for computing landscape metrics. Landsat imagery were analysed using Arcmap 10.7.1 and ENVI 5.3 software. The landscape of the Ramsar site is composed by the natural land (forests, savannahs, swamp formations), semi-natural land (plantations), anthropized land (agriculture lands, built-up area), and water land. These ecosystems have changed according to different trends 1990–2000, 2000–2020 and 1990–2020. The agricultural land showed an increasing trend of 143%, following by the built up area (37%). From 1990 to 2020, a decreasing of 45% has been observed in the savannah land, plantation land (41%), forest land (30%) and swampy land (17%). Also, the Ramsar site ecological context is at medium level despite the increasing of the landscape Ecological Risk Index: 0.1899, 0.2128, and 0.2165 in 1990, 2000, and 2020, respectively. Between 1990 and 2000, the creation process occurred in the built-up area and agriculture land, attrition within forest and plantation classes, dissection in swampy land, aggregation for savannah and shrinkage in water area. From 2000 to 2020, the agriculture land and swampy land continued to experience the same spatial transformation processes respectively. Dissection has observed within the forest land, attrition in water area, and aggregation for built-up area. The perforation process has observed within plantation, and fragmentation in Savannah. Finally, the development of agricultural activities and built-up areas are leading to change in the spatial structure of the Ramsar site landscape. To better conserve the biodiversity of these area, it will be necessary to characterize the still natural ecosystems. This will make it possible to propose a comprehensive management plan that integrates the agricultural and urbanization policy of the government, and the sustainable development goals.